A method for preparing high-entropy alloy tool coating with high wear resistance

By using magnetron sputtering technology on the tool surface, the TiAlSiCrN high-entropy alloy nitride coating was prepared, and combined with SiCrC layer and low-temperature heat treatment, the wear resistance and service life of traditional tools when processing difficult materials was solved, achieving efficient Tool protection and machining performance improvement.

CN118166323BActive Publication Date: 2025-02-11SOUTHWEAT UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410293433.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2025-02-11
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

When traditional tools process difficult materials, wear resistance and service life are reduced due to excessive cutting temperature and rapid heating rate. The existing coating technology has shortcomings in composition uniformity and controllability.

Method used

Magnetically controlled sputtering technology is used to prepare TiAlSiCrN high-entropy alloy nitride coating using a single TiAlSiCr alloy target, and the SiCrC layer is sputtered and deposited on the tool surface, and then the high-entropy alloy nitride coating is plating, combining low temperature and Heat treatment is used to enhance the bonding and wear resistance of the coating.

Benefits of technology

It significantly improves the wear resistance and service life of the tool, has high controllability and good stability, and is suitable for mass production and industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118166323B_ABST
    Figure CN118166323B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a high-entropy alloy tool coating with high wear resistance, comprising: using single elements Si, Al, Cr, and Ti as raw materials, smelting and preparing a TiAlSiCr alloy cathode target; using the prepared TiAlSiCr alloy cathode target to sputter and deposit a TiAlSiCrN high-entropy coating on the surface of the tool. The present invention adopts a magnetron sputtering process, uses a single TiAlSiCr alloy target, prepares a TiAlSiCrN high-entropy alloy nitride coating, and applies it to the surface of a tool substrate, thereby improving the wear resistance of the tool and extending its service life. The preparation process has good controllability and high stability, and is convenient for mass production and industrial promotion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating material preparation, and more specifically, the invention relates to a method for preparing a high-entropy alloy tool coating with high wear resistance. Background Art

[0002] The rapid development of modern manufacturing industry has placed higher and higher requirements on mechanical processing, and high-speed dry cutting processing technology has become the focus of people's attention. The application of difficult-to-process materials such as titanium alloys, stainless steel and composite materials, as well as the introduction of high-speed dry cutting technology, poses a huge challenge to the performance of processing tools. Problems such as excessive cutting temperature and excessive heating rate have caused the service life of traditional tools to drop sharply. Coating technology can effectively improve the hardness and wear resistance of the tool surface without changing its matrix plasticity and toughness, thereby giving the tool better cutting performance. At the same time, it can save the overall production cost of the tool to the greatest extent. Therefore, coated tools are increasingly widely used.

[0003] At present, commonly used tool coatings include nitrides, borides, oxides and diamonds, and conventional preparation methods can be divided into two categories: chemical vapor deposition (CVD) and physical vapor deposition (PVD). The CVD process needs to be carried out in a high temperature environment, which may affect the tool substrate. In contrast, the PVD process is a low-temperature preparation process and has greater advantages in the field of tool coating preparation. This method uses the magnetron sputtering technology (MS) in the PVD preparation process. The magnetron sputtering technology has the advantages of high sputtering rate, good film-base bonding, and simple equipment operation, and is the first choice for coating technology. According to the number of targets used, it can be divided into single target and multi-target. The use of multiple targets to prepare multi-component coatings is complicated because each target is independent of each other and needs to be controlled separately. The composition of the obtained coating will fluctuate, and it is impossible to ensure that the composition of each region on the substrate surface is uniform; the use of a single alloy target to prepare a multi-component coating has high controllability and good stability, and it is easy to prepare a coating with uniform composition in each region on the substrate surface.

[0004] High entropy alloys are made of five or more alloys and have excellent mechanical properties, corrosion resistance, thermal stability, etc. Among them, high entropy nitride coatings show good application prospects in the field of tool processing. The TiAlSiCrN coating proposed in this method is a new type of high entropy nitride coating. It is based on the TiN cemented carbide coating, and Al, Si, and Cr elements are added to make it easier to form a bcc phase, thus showing high strength and high hardness, that is, it has the structure and performance characteristics of high entropy alloys, which can significantly increase the wear resistance of the tool, extend the tool life, and improve the processing efficiency. Summary of the invention

[0005] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0006] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a high-entropy alloy tool coating with high wear resistance is provided, comprising the following steps:

[0007] Step 1: Using simple Si, Al, Cr and Ti as raw materials, smelting and preparing TiAlSiCr alloy cathode target;

[0008] Step 2: Using the prepared TiAlSiCr alloy cathode target, sputtering deposits a TiAlSiCrN high entropy coating on the surface of the tool.

[0009] Preferably, in the step 1, the mass fraction of elemental Si is 5-15%, the mass fraction of elemental Al is 2-10%, the mass fraction of elemental Cr is 3-20%, and the rest is elemental Ti.

[0010] Preferably, the specific method for smelting and preparing the TiAlSiCr alloy cathode target comprises: placing elemental Si, Al, Cr, and Ti into a vacuum electromagnetic induction water-cooled copper crucible smelting equipment, introducing Ar into the vacuum chamber as a protective gas, melting and magnetically stirring, then pouring the molten liquid into a mold, and cooling to obtain the TiAlSiCr alloy cathode target.

[0011] Preferably, the vacuum degree of the vacuum chamber is 260-300Pa.

[0012] Preferably, in said step 1, during smelting, induction heating is performed using a complete set of medium frequency induction heating power supply of model SPZ-110.

[0013] Preferably, the specific method of step 1 includes:

[0014] During smelting, mica sheets are used to fill the gaps between the petals of the crucible, and high-temperature resistant insulating tape is wrapped around the outside of the crucible to prevent the molten material from leaking out; the surface of the metal material is polished to remove the surface oxide, and then Ti, Al, Si, and Cr metal raw materials are weighed according to the composition design, and ultrasonically cleaned in an alcohol solution for 10 to 20 minutes to remove impurities and oil stains on the metal surface; finally, materials are placed in the crucible in the order of Ti, Cr, Al, and Si;

[0015] At the beginning of smelting, turn on the power first and keep it for 1 to 3 minutes to preheat the equipment; then observe the state of the metal in the crucible at the equipment observation window, and slowly increase the power while observing; when it is observed that the Al block begins to melt and gradually forms a molten pool, the power at this time has reached 25kW; when the power is continued to increase to 55kW, obvious signs of stirring are observed in the molten pool, the Ti rod at the bottom has melted, and the molten metal liquid formed with Al wraps the Si block and Cr block for a period of time, waiting for Si and Cr to be completely melted; continue to increase the power to 80kW, and observe that only the liquid phase exists in the crucible, the stirring speed of the metal liquid is accelerated, and it gradually breaks away from the contact with the crucible wall and is in a suspended state; at this time, prepare for casting, control the flip rod outside the vacuum chamber to realize the flip of the crucible, so that the melt in the crucible falls into the mold, and then reduce the power to the power start power. After the power is turned off, continue to cool with cooling water. After 30 minutes, turn off the cooling water, vent the vacuum chamber, and take out the smelting product.

[0016] Preferably, in step 1, the diameter of the TiAlSiCr alloy cathode target is 80-120 mm and the thickness is 5-7 mm.

[0017] Preferably, in step 2, before sputtering and depositing the TiAlSiCrN high entropy coating on the tool surface, the tool surface is first cleaned, including ultrasonic cleaning in acetone and alcohol for 5 to 20 minutes respectively; then the cleaned tool is mounted on a sample holder with the blade facing upward, and the sample holder is placed in a vacuum chamber.

[0018] Preferably, in the step 2, after the sample holder is placed in the vacuum chamber, the mechanical pump and the molecular pump are started in sequence to evacuate the deposition device, and the vacuum degree is 4×10 -3 ~8×10 -3 Pa; argon gas is introduced into the vacuum chamber to perform sputtering cleaning on the sample surface. After the sputtering cleaning is completed, nitrogen gas is introduced into the vacuum chamber to perform sputtering coating on the surface of the tool blade.

[0019] Preferably, in step 2, the sputtering coating process parameters include: nitrogen flow rate of 50-150 sccm, power supply voltage of 500 V, current of 0.2-0.6 A, working gas pressure of 0.5-1.0 Pa, and sputtering time of 30-120 min.

[0020] In order to further improve the wear resistance of the tool after the coating is plated, before performing step 2 of sputtering and depositing the TiAlSiCrN high entropy coating, a SiCrC layer is sputtered and deposited on the surface of the tool, and then the TiAlSiCrN high entropy coating is sputtered and deposited, and finally post-processing is performed to obtain a tool with a TiAlSiCrN high entropy coating, wherein the specific method of sputtering and depositing the SiCrC layer on the surface of the tool includes:

[0021] The tool that had been ultrasonically cleaned with acetone and alcohol for 5 to 20 minutes was placed in a sputtering device. Si and Cr targets were used as targets. The vacuum chamber was evacuated to 4 × 10 -3 ~8×10 -3 Pa, argon gas is introduced into the vacuum chamber to sputter clean the sample surface. After sputter cleaning, the introduction rate and time of argon gas are controlled to make the working pressure of the vacuum chamber 0.1-0.3Pa, the power of Si target is set to 100-300W, the power of Cr target is set to 150-300W, the negative bias voltage is set to -500--300V, the power supply voltage is 400-800V, acetylene is introduced as C source, the flow rate of acetylene is 200-600sccm, the sputtering time is 40-100min, and a SiCrC layer is obtained on the tool surface.

[0022] The post-treatment method includes: after the TiAlSiCrN high entropy coating is plated, the vacuum state is maintained for 30 to 60 minutes, and then the tool is taken out, and the tool is placed in a cryogenic treatment box, and the temperature is reduced to -100 to -180°C at a cooling rate of 10 to 20°C / min, and the temperature is kept for 30 to 100 seconds, and then taken out;

[0023] After being taken out, the tool is placed in a box furnace, heated to 200-400°C at a heating rate of 5-10°C / min, kept warm for 2-6 minutes, and naturally cooled after being taken out to obtain a post-treated tool with a TiAlSiCrN high entropy coating.

[0024] The present invention has at least the following beneficial effects:

[0025] The present invention adopts magnetron sputtering technology and uses a single TiAlSiCr alloy target to prepare a TiAlSiCrN high entropy alloy nitride coating, and applies it to the surface of a tool substrate to improve the wear resistance of the tool and extend its service life. The preparation process has good controllability and high stability, and is convenient for mass production and industrial promotion.

[0026] The present invention uses a Si target and a Cr target in combination with acetylene to sputter and deposit a SiCrC layer on the surface of the tool before using a TiAlSiCr alloy target to sputter and plate a high entropy alloy nitride coating on the surface of the tool. Then, the high entropy alloy nitride coating is plated. The SiCrC layer itself has extremely high hardness and wear resistance. At the same time, the SiCrC layer is also a transition layer between the surface of the tool and the high entropy alloy nitride coating, which reduces the stress between the surface of the tool and the high entropy alloy nitride coating and improves the bonding force of the high entropy alloy nitride coating on the surface of the tool. Finally, low temperature and heat treatment are performed, the low temperature treatment is used to release the stress of the film layer, and the heat treatment improves the bonding force between the SiCrC layer and the high entropy alloy nitride coating. As a result, such a technical solution further improves the protection of the tool surface, and further improves the wear resistance and service life of the tool.

[0027] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of sampling position of TiAlSiCr alloy cathode target prepared in Example 1;

[0029] Figure 2 This is a physical picture of the TiAlSiCr alloy cathode target prepared in Example 1;

[0030] Figure 3 This is a photo of a tool having a high-entropy alloy tool coating with high wear resistance obtained by plating in Example 1;

[0031] Figure 4 A schematic diagram of a cutting test on a plated tool of Example 1;

[0032] Figure 5 for Figure 1 The metallographic structure of the sample at S1 in the middle observed under a 500x optical microscope;

[0033] Figure 6 for Figure 1 The metallographic structure of the sample at S2 observed under a 500x optical microscope;

[0034] Figure 7 for Figure 1 The metallographic structure of the sample at S3 observed under a 500x optical microscope;

[0035] Figure 8 for Figure 1 The metallographic structure of the sample at S4 observed under a 500x optical microscope;

[0036] Fig. 9 for Figure 1 EDS surface scanning results of the sample at S1;

[0037] Fig.10 for Figure 1 EDS surface scanning results of the sample at S2;

[0038] Fig.11 for Figure 1 EDS surface scanning results of the sample at S3;

[0039] Fig.12 for Figure 1 EDS surface scanning results of the sample at S4;

[0040] Fig.13 The sampling position for EDS test of the surface composition of the coated tool prepared in Example 1;

[0041] Fig.14 for Fig.13 EDS test results of the sampling position;

[0042] Fig.15 This is a macroscopic photograph of the coated tool prepared in Example 1 after the cutting test;

[0043] Fig.16 for Fig.15 Enlarged image of the middle dashed box;

[0044] Fig.17 This is a physical picture of the TiAlSiCr metal block obtained by smelting in Comparative Example 1;

[0045] Fig.18 This is a physical picture of the TiAlSiCr metal block obtained by smelting in Comparative Example 1 from another angle. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0047] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0048] Example 1

[0049] This embodiment provides a method for preparing a high-entropy alloy tool coating with high wear resistance, comprising the following steps:

[0050] Step 1, putting Si with a mass fraction of 7.15%, Al with a mass fraction of 3.02%, Cr with a mass fraction of 5.81% and Ti with a mass fraction of 84.02% into a vacuum electromagnetic induction water-cooled copper crucible smelting equipment, the vacuum degree is 280Pa, and the induction heating is powered by a complete set of medium-frequency induction heating power supply of the SPZ-110 model, and the output power is 80kW; Ar is introduced into the vacuum chamber as a protective gas, and the melting is magnetically stirred, and then the smelted molten metal is poured into a mold, and cooled to obtain a TiAlSiCr alloy cathode target, wherein the diameter of the TiAlSiCr alloy cathode target is 100mm and the thickness is 6mm;

[0051] The specific methods of smelting include:

[0052] During smelting, fill the gaps between the petals of the crucible with mica sheets, and wrap the outside of the crucible with high-temperature resistant insulating tape to prevent the molten material from leaking out; grind and polish the surface of the metal material to remove the surface oxide, then weigh Ti, Al, Si, and Cr metal raw materials according to the composition design, and put them into an alcohol solution for ultrasonic cleaning for 15 minutes to remove impurities and oil stains on the metal surface; finally, put the materials into the crucible in the order of Ti, Cr, Al, and Si;

[0053] At the beginning of smelting, turn on the power first and keep it for 1 minute to preheat the equipment; then observe the state of the metal in the crucible at the equipment observation window, and slowly increase the power while observing; when it is observed that the Al block begins to melt and gradually forms a molten pool, the power at this time has reached 25kW; when the power is continued to increase to 55kW, obvious signs of stirring are observed in the molten pool, the Ti rod at the bottom has melted, and the molten metal liquid formed with Al wraps the Si block and Cr block for a period of time, waiting for Si and Cr to be completely melted; continue to increase the power to 80kW, and observe that there is only liquid phase in the crucible, the stirring speed of the metal liquid is accelerated, and it gradually breaks away from the contact with the crucible wall and is in a suspended state; at this time, prepare for casting, control the flip rod outside the vacuum chamber to realize the flip of the crucible, so that the melt in the crucible falls into the mold, and then reduce the power to the power start power. After the power is turned off, continue to cool with cooling water. After 30 minutes, turn off the cooling water, vent the vacuum chamber, and take out the smelting product.

[0054] The view of the TiAlSiCr alloy cathode target obtained by melting and cooling in this embodiment is as follows Figure 2 As shown in the figure, it can be seen that the surface of the TiAlSiCr alloy cathode target is smooth and defect-free, showing a silvery white luster. According to the experimental results, the components of the smelting product are evenly distributed. This is because the metal material is completely melted and the molten metal liquid in the crucible is magnetically stirred, so that the alloy with better surface quality is finally obtained; Figure 1As shown, the TiAlSiCr alloy cathode target was sampled, and the sampling positions were marked as S1, S2, S3, and S4 in sequence. The microstructures of the samples at S1, S2, S3, and S4 observed under a 500x optical microscope were as follows: Figure 5 , Figure 6 , Figure 7 , Figure 8 As shown, it can be seen that the alloy structures of the four groups of samples are evenly distributed, without obvious voids, segregation and other phenomena, indicating that the smelted alloy structure distribution is relatively uniform; Figure 9-12 These are the EDS surface scanning results of samples S1 to S4. It can be seen that the four elements Ti, Al, Si, and Cr are distributed evenly in the four groups of samples. Figure 5-Figure 8 and Figure 9-12 The results show that the TiAlSiCr alloy smelted in a water-cooled copper crucible has uniform structure and composition distribution, and can be used as a sputtering target in the magnetron sputtering coating preparation process, and is expected to prepare a coating with uniform composition.

[0055] Step 2: Clean the surface of the tool, including ultrasonic cleaning in acetone and alcohol for 10 minutes respectively; then install the cleaned tool on the sample holder, with blades No. 5 to 8 facing upward (the tool used in this embodiment has two sides, numbered 1-8 blade faces, wherein blades No. 1 to 4 are on one side, and blades No. 5 to 8 are on the other side, and blades No. 5 to 8 are arranged as follows: Figure 3 As shown in the figure, the blades 5 to 8 are arranged in a clockwise direction), and the sample holder is placed in the vacuum chamber; the mechanical pump and the molecular pump are started in sequence to evacuate the deposition device, and the vacuum degree is 6×10 -3 Pa; argon gas is introduced into the vacuum chamber to sputter clean the sample surface to further remove the contaminants on the tool surface; after the sputter cleaning is completed, nitrogen gas is introduced into the vacuum chamber, the nitrogen flow rate is 100sccm, the power supply voltage is 500V, the current is 0.4A, the working pressure is 1.0Pa, the sputtering time is 120min, and the surfaces of the blades 5 to 8 of the tool are sputter coated. Figure 3 As shown in FIG. 1 , a high-entropy alloy tool coating with high wear resistance is obtained on the tool surface. The schematic diagram of the sputtering device used in this embodiment is shown in FIG. Fig.17 shown.

[0056] Fig.13 This is the EDS sampling position of the coated tool obtained in this embodiment. Fig.14 This is the EDS test result of this position. The results show that the deposited coating is composed of TiAlSiCrN.

[0057] like Figure 4As shown in the figure, the coated tool is subjected to a cutting test. When the tool wear reaches the expected value, an alarm is issued, cutting is stopped and the cutting length at this time is recorded. The macroscopic photo of the coated tool after the cutting test is shown in the figure. Fig.15 As shown, Fig.15 The dotted box in the image is enlarged as shown in Fig.16 It can be seen that there is no serious wear and chipping at the cutting edge, and the coating is still well attached to the substrate, proving that the TiAlSiCrN coating has good film-substrate bonding.

[0058] Some blade cutting test data are shown in the table below, where blades with blade number 2 and blade number 3 are not coated, while blade number 8 is coated, indicating that the cutting effect of coated tools is significantly better than that of uncoated tools.

[0059] Cutting test data of some coated tool edges

[0060]

[0061] Example 2

[0062] This embodiment provides a method for preparing a high-entropy alloy tool coating with high wear resistance, wherein the smelting method of the TiAlSiCr alloy cathode target is the same as that of Embodiment 1, except that the SiCrC layer is first sputtered and deposited on the tool surface in this embodiment. The specific method includes:

[0063] The tool that had been ultrasonically cleaned with acetone and alcohol for 10 min was placed in a sputtering device. Si and Cr targets were used as targets. The vacuum chamber was evacuated to 6×10 -3 Pa, argon gas is introduced into the vacuum chamber to sputter clean the sample surface. After sputter cleaning, the introduction rate and time of argon gas are controlled to make the working pressure of the vacuum chamber 0.1Pa, the power of Si target is set to 150W, the power of Cr target is set to 200W, the negative bias voltage is set to -500V, the power supply voltage is 600V, acetylene is introduced as C source, the acetylene flow rate is 200sccm, the sputtering time is 60min, and a SiCrC layer is obtained on the tool surface.

[0064] Then nitrogen gas was introduced into the vacuum chamber with a nitrogen flow rate of 100 sccm, a power supply voltage of 500 V, a current of 0.4 A, a working gas pressure of 1.0 Pa, and a sputtering time of 120 min. The surfaces of cutting edges No. 5 to 8 of the tools were sputtered to obtain a TiAlSiCrN high entropy coating on the surface of the SiCrC layer.

[0065] After the TiAlSiCrN high entropy coating is plated, the vacuum state is maintained for 30 minutes, and then the tool is taken out and placed in a cryogenic treatment box, cooled to -150°C at a cooling rate of 10°C / min, kept warm for 30 seconds, and then taken out;

[0066] After being taken out, the tool was placed in a box furnace, heated to 300°C at a heating rate of 5°C / min, kept warm for 3 minutes, and naturally cooled after being taken out to obtain a post-treated tool with a TiAlSiCrN high entropy coating.

[0067] Example 3

[0068] This embodiment provides a method for preparing a high-entropy alloy tool coating with high wear resistance, wherein the smelting method of the TiAlSiCr alloy cathode target is the same as that of Embodiment 1, except that the SiCrC layer is first sputtered and deposited on the tool surface in this embodiment. The specific method includes:

[0069] The tool that had been ultrasonically cleaned with acetone and alcohol for 10 min was placed in a sputtering device. Si and Cr targets were used as targets. The vacuum chamber was evacuated to 6×10 -3 Pa, argon gas is introduced into the vacuum chamber to sputter clean the sample surface. After sputter cleaning, the introduction rate and time of argon gas are controlled to make the working pressure of the vacuum chamber 0.3Pa, the power of Si target is set to 200W, the power of Cr target is set to 250W, the negative bias voltage is set to -500V, the power supply voltage is 500V, acetylene is introduced as C source, the acetylene flow rate is 400sccm, the sputtering time is 30min, and a SiCrC layer is obtained on the tool surface.

[0070] Then nitrogen gas was introduced into the vacuum chamber with a nitrogen flow rate of 100 sccm, a power supply voltage of 500 V, a current of 0.4 A, a working gas pressure of 1.0 Pa, and a sputtering time of 120 min. The surfaces of cutting edges No. 5 to 8 of the tools were sputtered to obtain a TiAlSiCrN high entropy coating on the surface of the SiCrC layer.

[0071] After the TiAlSiCrN high entropy coating is plated, the vacuum state is maintained for 60 minutes, and then the tool is taken out and placed in a cryogenic treatment box, cooled to -180°C at a cooling rate of 20°C / min, kept warm for 30 seconds, and then taken out;

[0072] After being taken out, the tool was placed in a box furnace, heated to 400°C at a heating rate of 10°C / min, kept warm for 6 minutes, and then naturally cooled after being taken out to obtain a post-treated tool with a TiAlSiCrN high entropy coating.

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 1 is that the smelting method used in step 1 is: Ti, Al, Si, and Cr metal raw materials of the same quality as those in Example 1 are selected, wherein Ti is sponge titanium, and the sponge titanium is placed at the bottom and the top of the crucible, and the Al, Si, and Cr metal raw materials are placed in the middle of the sponge titanium. During smelting, there is no preheating, and it is directly heated to 38 kW. The power is increased to 80 kW in 25 minutes, and the metal raw materials are still not completely melted. Fig.17 and Fig.18 As shown in the figure, since the comparative example was not preheated, the heating power and the heating rate were not well matched, and the metal block in the crucible could not be completely melted to form a liquid alloy, so the subsequent pouring process could not be completed smoothly, and the complete alloy material could not be processed into an alloy cathode target of the required size.

[0075] Comparative Example 2

[0076] Compared with Example 2, the difference in this comparative example is that after the TiAlSiCrN high entropy coating is obtained on the surface of the SiCrC layer, a natural cooling method is adopted without low-temperature treatment and heat treatment. The remaining processes are the same as those in Example 2.

[0077] Comparative Example 3

[0078] Compared with Example 2, the difference in this comparative example is that after the TiAlSiCrN high entropy coating is obtained on the surface of the SiCrC layer, it is naturally cooled to room temperature and then heat treated. The heat treatment process is the same as that of Example 2, and no low-temperature treatment is performed. The remaining processes are the same as those of Example 2.

[0079] Comparative Example 4

[0080] Compared with Example 2, the difference in this comparative example is that after the TiAlSiCrN high entropy coating is obtained on the surface of the SiCrC layer, no heat treatment is performed after the low-temperature treatment. The low-temperature treatment process is the same as that of Example 2, and the remaining processes are the same as those of Example 2.

[0081] like Figure 4 As shown, the cutting tools sputtered to obtain TiAlSiCrN high entropy coatings in Example 1, Example 2, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were respectively installed on the cutting device for blade cutting test. The test objects were all No. 8 blade surfaces, and the following table was obtained:

[0082]

[0083] It can be seen from the above table that the blade surface of the tool plated in Example 2 has better cutting performance than that in Example 1 and Comparative Examples 2 to 4, indicating that Example 2 adopts the process of first sputtering the SiCrC layer, then plating the TiAlSiCrN high entropy coating, and finally performing low-temperature treatment and heat treatment. The tool obtained by this method has higher wear resistance.

[0084] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.

[0085] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing a high-entropy alloy tool coating with high wear resistance, characterized in that: The following steps are involved: Step 1: Using simple Si, Al, Cr and Ti as raw materials, smelting and preparing TiAlSiCr alloy cathode target; Step 2: using the prepared TiAlSiCr alloy cathode target, sputtering and depositing a TiAlSiCrN high entropy coating on the surface of the tool; In the step 1, the mass fraction of elemental Si is 5-15%, the mass fraction of elemental Al is 2-10%, the mass fraction of elemental Cr is 3-20%, and the remainder is elemental Ti; In the step 1, the specific method for smelting and preparing the TiAlSiCr alloy cathode target material comprises: placing elemental Si, Al, Cr, and Ti into a vacuum electromagnetic induction water-cooled copper crucible smelting equipment, introducing Ar as a protective gas into the vacuum chamber, melting and magnetically stirring, then pouring the molten liquid into a mold, and cooling to obtain the TiAlSiCr alloy cathode target material; The specific method of step one includes: During smelting, fill the gaps between the petals of the crucible with mica sheets, and wrap the outside of the crucible with high-temperature resistant insulating tape to prevent the smelt from leaking out; grind and polish the surface of the metal material to remove the surface oxide, then weigh Ti, Al, Si, and Cr metal raw materials according to the composition design, and put them into an alcohol solution for ultrasonic cleaning for 10 to 20 minutes to remove impurities and oil stains on the metal surface; finally, put the materials into the crucible in the order of Ti, Cr, Al, and Si; At the beginning of smelting, turn on the power first and keep it for 1~3min to preheat the equipment; then observe the state of the metal in the crucible at the equipment observation window, and slowly increase the power while observing; when the Al block is observed to begin to melt and gradually form a molten pool, the power at this time has reached 25kW; when the power is continued to increase to 55kW, obvious signs of stirring are observed in the molten pool, the Ti rod at the bottom has melted, and the molten metal liquid formed with Al wraps the Si block and Cr block for a period of time, waiting for Si and Cr to be completely melted; continue to increase the power to 80kW, and observe that there is only liquid phase in the crucible, the stirring speed of the metal liquid is accelerated, and it gradually breaks away from the contact with the crucible wall and is in a suspended state; at this time, prepare for casting, control the flip rod outside the vacuum chamber to realize the flip of the crucible, so that the melt in the crucible falls into the mold, and then reduce the power to the power start power. After the power is turned off, continue to cool with cooling water. After 30 minutes, turn off the cooling water, vent the vacuum chamber, and take out the smelting product; Before performing step 2 of sputtering and depositing the TiAlSiCrN high entropy coating, a SiCrC layer is sputtered and deposited on the surface of the tool, and then the TiAlSiCrN high entropy coating is sputtered and deposited, and finally post-processing is performed to obtain a tool with a TiAlSiCrN high entropy coating, wherein the specific method of sputtering and depositing the SiCrC layer on the surface of the tool includes: The tool that had been ultrasonically cleaned with acetone and alcohol for 5-20 min was placed in a sputtering device. Si and Cr targets were used as targets. The vacuum chamber was evacuated to 4×10 -3 ~8×10 -3 After 1000 Pa, argon gas is introduced into the vacuum chamber to sputter clean the sample surface. After the sputter cleaning is completed, the introduction rate and time of argon gas are controlled to make the working pressure of the vacuum chamber 0.1~0.3Pa, the power of the Si target is set to 100~300W, the power of the Cr target is set to 150~300W, the negative bias voltage is set to -500~-300V, the power supply voltage is 400~800V, acetylene is introduced as the C source, the flow rate of acetylene is 200~600sccm, the sputtering time is 40~100min, and a SiCrC layer is obtained on the tool surface; The post-treatment method includes: after the TiAlSiCrN high entropy coating is plated, the vacuum state is maintained for 30 to 60 minutes, and then the tool is taken out, and the tool is placed in a cryogenic treatment box, and the temperature is reduced to -100 to -180°C at a cooling rate of 10 to 20°C / min, and the temperature is kept for 30 to 100 seconds, and then taken out; After being taken out, the tool is placed in a box furnace, heated to 200-400°C at a heating rate of 5-10°C / min, kept warm for 2-6 minutes, and naturally cooled after being taken out to obtain a post-treated tool with a TiAlSiCrN high entropy coating.

2. The method for preparing a high-entropy alloy tool coating with high wear resistance as claimed in claim 1, characterized in that: In the step 1, the vacuum degree of the vacuum chamber is 260-300 Pa.

3. The method for preparing a high-entropy alloy tool coating with high wear resistance as claimed in claim 1, characterized in that: In the step 1, during smelting, a complete set of medium frequency induction heating power supply of model SPZ-110 is used for induction heating.

4. The method for preparing a high-entropy alloy tool coating with high wear resistance as claimed in claim 1, characterized in that: In the step 1, the diameter of the TiAlSiCr alloy cathode target is 80-120 mm and the thickness is 5-7 mm.

5. The method for preparing a high-entropy alloy tool coating with high wear resistance as claimed in claim 1, characterized in that: In the step 2, before sputtering and depositing the TiAlSiCrN high entropy coating on the tool surface, the tool surface is first cleaned, including ultrasonic cleaning in acetone and alcohol for 5 to 20 minutes respectively; then the cleaned tool is mounted on a sample holder with the blade facing upward, and the sample holder is placed in a vacuum chamber.

6. The method for preparing a high-entropy alloy tool coating with high wear resistance as claimed in claim 5, characterized in that: In step 2, after the sample holder is placed in the vacuum chamber, the mechanical pump and the molecular pump are started in sequence to evacuate the deposition device to a vacuum degree of 4×10 -3 ~8×10 -3 Pa; argon gas is introduced into the vacuum chamber to perform sputtering cleaning on the sample surface. After the sputtering cleaning is completed, nitrogen gas is introduced into the vacuum chamber to perform sputtering coating on the surface of the tool blade.

7. The method for preparing a high-entropy alloy tool coating with high wear resistance as claimed in claim 1, characterized in that: In the step 2, the sputtering coating process parameters include: nitrogen flow rate of 50-150 sccm, power supply voltage of 500 V, current of 0.2-0.6 A, working gas pressure of 0.5-1.0 Pa, and sputtering time of 30-120 min.

Citation Information

Patent Citations

  • Method for adopting high-entropy alloy coating film on tool

    CN110295347A

  • Method for preparing multi-element and multilayer coating on tool surface

    CN110408903A